Measuring Video Game Engagement Through Gameplay Reviews. (August 2014) - Kirschner, David; Williams, J. Patrick
Aim . In this article, we develop a method, that we call thegameplay review method, for measuring players'engagement with digital games through players'interactions withvideo recordings of their own gameplay. Method . The gameplay review method arose from a microsociological study of the gameplay of eight young adults who each played approximately 20 hours of WORLD OF WARCRAFT over a 3-month period in 2012. Using data from in-depth interviews and audiovisual recordings of one of the eight participants, this article focuses on how the method leveraged participants'knowledge of theirexperiences and ties that knowledge tomeasures of engagement . We outline the method's four-step process (producing Level I data, analyzing Level I data, producing Level II data, analyzing Level II data) to guide the generation and analysis of rich video data. The method involves focused discussions on selectedrecorded segments of participants' gameplay and is a means of connecting game design with bothempirical andinterpretive data. Results . We show how, as participants progress, they learn aboutgame design features and deepen theirunderstanding of games . We found that participants' developingperceptions of, andrelationships to, design features affect theirengagement with digital games. Conclusion . The gameplay review method is significant in its ability tomeasure engagement by dealingexplicitly withempirical andinterpretive data.